Finite Element Simulation of Newtonian and Non-Newtonian Fluid through the Parallel Plates Affixed with Single Screen (European Journal of Pure and Applied Mathematics, 2020)
In the contemporary research article we have performed a numerical investigation of the non-Newtonian fluid flow through a rectangular channel with a fixed solid screen devoted at the angles 100 to 450 degrees. We have employed the power-law model for shear thickening and shear thinning fluids with the high Reynolds number between 1000 and 10,000. The obstacle has been solved by putting in the Galerkinâ€™s least square strategy of the finite element method and the procedure has been carried out utilizing the commercial software COMSOL Multiphysics. Various flow properties such as 'maximum flow rate' and 'pressure' have been discussed in the terms of the Reynolds number and also using the linear and quadratic regressions in order to establish the relationship between them for the future analysis. Moreover the impact of turning screen in the shape of increment in the maximum flow rate and pressure is checked in terms of Reynolds number andÂ  Satisfactory results are gained in comparison with the results available in the literature.